(untitled) (Homiletic, 2021)
Military suicides have dramatically increased over the last twenty years. In response, much energy and expense have been focused on suicide prevention, as well as training chaplains and other caregivers. Despite the comprehensive intentions of these efforts, little focus has been placed on the ways in which worship and preaching might contribute to abating the crisis. The purpose of this article is to examine some critical areas for consideration in creating sermons that address the threat of suicide for the Army chapel community. The difficulties of preaching to desperate listeners are examined along with the prevalent myths associated with suicide. The selection of language and presentation of the message are each discussed along with the pitfalls of certain atonement hermeneutics. Suggestions for biblical texts, including use of the psalms, are reviewed. The article concludes with further recommendations for better addressing suicide from the pulpit.